Glutamatergic Response to Heat Pain Stress in Schizophrenia. (23rd September 2017) - Chiappelli, Joshua; Shi, Qiaoyun; Wijtenburg, Sarah Andrea; Quiton, Raimi; Wisner, Krista; Gaston, Frank; Kodi, Priyadurga; Gaudiot, Christopher; Kochunov, Peter; Rowland, Laura M; Hong, Liyi Elliot
Abstract: Regulation of stress response involves top-down mechanisms of the frontal-limbic glutamatergic system. As schizophrenia is associated with glutamatergic abnormalities, we hypothesized that schizophrenia patients may have abnormal glutamatergic reactivity within the dorsal anterior cingulate cortex (dACC), a key region involved in perception of and reaction to stress. To test this, we developed a somatic stress paradigm involving pseudorandom application of safe but painfully hot stimuli to the forearm of participants while they were undergoing serial proton magnetic resonance spectroscopy to measure changes in glutamate and glutamine levels in the dACC. This paradigm was tested in a sample of 21 healthy controls and 23 patients with schizophrenia. Across groups, glutamate levels significantly decreased following exposure to thermal pain, while ratio of glutamine to glutamate significantly increased. However, schizophrenia patients exhibited an initial increase in glutamate levels during challenge that was significantly different from controls, after controlling for heat pain tolerance. Furthermore, in patients, the acute glutamate response was positively correlated with childhood trauma ( r = .41, P = .050) and inversely correlated with working memory ( r = −.49, P = .023). These results provide preliminary evidence for abnormal glutamatergic response to stress in schizophrenia patients, which may point toward novel approaches to understanding how stress contributes to the illness.